2016
DOI: 10.5301/jbm.5000196
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PTEN and Its Correlation with Proliferation Marker Ki-67 in Head and Neck Cancer

Abstract: Our data suggest that downregulation of PTEN and overexpression of Ki-67 may contribute to the initiation and progression of HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 76 publications
1
8
0
Order By: Relevance
“…Some researches revealed the significant association between no/low PTEN expression and T stage, N stage and/or grade [58,62]. However, there are studies where such relations were not found [61,63], similarly to us. On the other hand, in our study expression of PTEN was significantly associated with cancer site.…”
Section: Pten and Pptensupporting
confidence: 67%
“…Some researches revealed the significant association between no/low PTEN expression and T stage, N stage and/or grade [58,62]. However, there are studies where such relations were not found [61,63], similarly to us. On the other hand, in our study expression of PTEN was significantly associated with cancer site.…”
Section: Pten and Pptensupporting
confidence: 67%
“…The PI3K/AKT signaling pathway is a well-known pathway in the regulation of tumorigenesis, and is significantly activated in glioma [ 14 ]. PTEN contributes in antagonizing PI3K [ 15 ], thereby weakening AKT activation [ 16 ], which could suppress down-stream products thereby inducing cell cycle arrest in the G1 phase by increasing ki-67 expression [ 15 ] and decreasing cyclin D1 expression [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that the expression of PTEN was dramatically up-regulated. PTEN is an important negative regulator of AKT pathway, it can antagonize PI3K and then weaken the activation of AKT (Zhang et al, 2015 ; Ahmed et al, 2016 ). Therefore, the up-regulation of PTEN and down-regulation of PI3K further confirmed that AKT pathway could be inactivated by CT04.…”
Section: Discussionmentioning
confidence: 99%